POSSIBLE ROLE OF LIVER PROTEASOMES IN THE REALIZATION OF MECHANISMS OF TRANSPLANTATION TOLERANCE - G. A. Bozhok; Ya. D. Karpova; Yu. V. Lyupina; E. I. Legach; Yu. V. Bogomyagkova; T. P. Bondarenko; N. P. Sharova (Вестник трансплантологии и искусственных органов, 2011)
In contrast to the majority of organs in liver non-specific immunity predominates over adaptive one, and in response to the antigen presentation develops preferably not immune reaction but immunological tolerance. Tolerance is considered to provide some processes, such as apoptosis of reactive T-cells, immune deviation and active suppression of immune reactions. At the same time there are the grounds for believing that an important role in regulation of liver immune response is played by proteasomes, intracellular multiprotease protein complexes. This is confirmed by the fact of application of proteasome inhibitor bortezomib as immune suppressor in transplantology. Immune 26S- and 20S-proteoasomes participate in the formation of antigen oligopeptides and play a key role in T-cell immune response. It has been shown that the pool of proteasomes is subjected to significant changes during ontogenesis of immune competent organs. The changes in the pool of proteasosmes occur likely during the development of specific tolerance in transplantation too. The knowledge of the peculiarities of proteasome functioning and regularities of alterations of their shapes will enable the revealing of the mechanisms responsible for either graft rejection or acceptance.